Gamification in the English language class: analysis of pre-service teachers’ perceptions. - Fernández-Portero, Ignacio; Castillo-Rodríguez, Cristina Milagrosa (Ritsumeikan University, 2022)
An educative breakout is a modified version of the popular immersive entertainment experience of escape rooms, in which game elements and game design techniques are used in non-game contexts. In educational settings, it is usually used to teach content while developing cognitive skills to improve learners’ performance. This study used a mixed-methods research design to examine the effectiveness of a digital breakout to learn English as a Foreign Language (EFL) in higher education. Quantitative and qualitative data were collected through several forms and surveys so that the participants could express their perceptions about this learning experience. Results showed that pre-service English teachers (N = 95) had a positive attitude towards learning grammar-related content through complex games, riddles, and puzzles. Moreover, 95.8% of them would use this teaching method in the future and 90% completed all the challenges. Therefore, it can be concluded that a gamification-based approach can be an effective and motivating way to learn EFL in higher education.
Keywords: Profesores - Formación profesional; Gamificación; Inglés - Estudio y enseñanza - Estudiantes extranjeros; Pre-service teacher; Breakout; Gamification; EFL; Motivation